Determinan Rujukan Non Spesialistik Dengan Kriteria TACC di FKTP Kabupaten Batang Hari Tahun 2022 - Bathari Yanthi; Julita Hendratini; Dwi Handono Sulistyo (Jurnal Jaminan Kesehatan Nasional, 2023)
The capacity of primary healthcare as gatekeepers to handle 144 comprehensive and independent primary diagnoses is a form of strengthening primary healthcare facilities for the implementation of both quality and cost control. Non-specialist Referral diagnoses with TACC (Time, Age, Comorbidity, Complication) included in the 4A competency level for primary doctors allows the doctors to refer patients to Advanced Referral Health Facilities. This study aimed to identify the determinants that affect Non-Specialistist Referral with TACC in FKTP Batang Hari Regency. This research was a cross-sectional mixed-method study with a sequential explanatory design using primary doctors as the total sampling and heads of FKTP and National Health Insurance patients as sample representatives. The quantitative method using Chi-square analysis was used to determine the effect of each independent variable on the dependent variable. Qualitative analysis was carried out by quantitative data triangulation. The results of the statistical test show that there was a significant association between the availability of medical devices and drugs wNon-Specialististtist Referral with TACC (medical devices p=0.017, drugs p=0.002), while doctors’ knowledge, doctors’ competence, FKTP location, and type did not show a significant association. In-depth interviews revealed that patients’ request was one of the reasons for doctors’ referral. There is a significant association between the availability of medical devices and drugs with NonSpecialistst Referral with TACC supported by patients’ request for referral.